The role of CCR5 polymorphism in colorectal cancer and liver metastasis in the Tunisian population - Weslati, Marwa; Boughriba, Rahma; Ounissi, Donia; Hazgui, Meriam; Marghali, Sonia (Archives of Biological Sciences, 2021)
Paper description: Colorectal cancer results from the accumulation of genetic and epigenetic alterations and complex interactions between tumor cells and the tumor microenvironment. Understanding genetic differences in populations helps develop specific and more effective treatments. Research targeting C-C chemokine receptor type 5 (CCR5) (rs333) in both colorectal cancer and colorectal cancer liver metastases are inconclusive. We investigated the impact of this mutation in different stages. CCR5Δ32 reduced colorectal cancer risk; all metastases had wild type CCR5. Having a dysfunctional/repressed CCR5 receptor is unfavorable to colorectal cancer and colorectal cancer liver metastases development, CCR5Δ32 might protect against CRC development and dissemination. Abstract: Chemokines and their receptors are involved in cancer initiation and progression, including colorectal cancer (CRC) and liver metastasis formation. Our aim was to elucidate C-C chemokine receptor type 5 (CCR5) gene polymorphism (CCR5Δ32) impact on CRC and colorectal cancer liver metastases (CRLM) occurrence risk. We analyzed the CCR5 gene mutational status in 108 primary CRC cases, 35 CRLM and 248 healthy individuals, and evaluated CCR5 expression in healthy tissue and tumors. Rare allele “Δ32” was more frequent in controls (7.2% vs 2.8% in CRC). All 35 metastases had wild-type CCR5. Our analysis showed that CCR5 wild type has a significant risk of 2.73-fold (95% CI=1.22-7.31) to cause CRC while Δ32 reduced the risks 0.36-fold (95% CI=0.13-0.82). For CRC, CCR5 correlated with left-sided tumors and liver metastases (P=0.040 and P= 0.039 respectively). As for CRLM, no correlation was found. Immunohistochemical profile analysis of CCR5 revealed a significant association with the male gender (P=0.049) and non-mucinous carcinomas (P< 0.001) in primary CRC. CCR5 expression revealed an association with the degree of tumor differentiation for both CRC and CRLM (P < 0.001). CCR5Δ32 might be a protective factor against CRC development and dissemination.